Poligami Pada Keluarga Terdekat Istri (Kajian Metode Hadis Tahlili Pada Hadis Poligami Keluarga Terdekat Istri) - Erwin Hafid (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Polygamy in the Wife's Closest Family (Study of the Tahlili Hadith Method on the Wife's Closest Family Polygamy Hadith)Polygamy is a reality that occurs in society with various kinds of pros and cons. Sometimes the permissibility of polygamy is not followed by comprehensive knowledge regarding its aspects, such as the permissibility and prohibition of polygamy/integration with anyone. Sometimes they practice polygamy in the wife's closest family, because of a lack of knowledge of these provisions. This study aims to examine the tahlili (analysis) of hadith regarding the prohibition of mixing women with their closest family. This research method is library research (literary study) with a qualitative research type, focusing on detailed analysis regarding the hadith which prohibits polygamy between women and their immediate family. Both from the aspect of sanad and matnya by using an approach to the science of hadith and the science of syarhu al-hadith in a tahlil way. This study found that from a quality aspect it can be ascertained that this hadith is included in the authentic hadith. Even though it has different editorials, there is no confusion in each of these editorials. In fact, this proves that this hadith has multiple narrators, and that means this hadith is aziz (narrated by two sanad lines). In this study, no asbab wurud was found. This hadith is also considered as the basis for the permissibility of the hadith for interpreting verses of the Qur'an, because in Surat an-Nisa verse 23 it is generally accepted except for brothers and sisters and in this hadith an additional (exception) is given, namely the prohibition of polygamy for wives and aunts. or vice versa. This hadith also contains wisdom about the importance of protecting the feelings of a woman who is married by prohibiting polygamy with the wife's closest family